Instrument Reliability Analysis - Fendik Saputra (CV. Publikasi Indonesia, 2025)
This study aims to analyze the reliability of research instruments used to measure the quality of education. The research instrument used was a questionnaire consisting of 20 items. Data were collected from 100 randomly selected respondents. Reliability analysis was conducted using the Cronbach's Alpha method. The results showed that the research instrument had high reliability, with a Cronbach's Alpha value of 0.85. This means that the research instruments are reliable for measuring education quality. This study has important implications for educational researchers and practitioners in developing reliable research instruments.